1996
DOI: 10.1074/jbc.271.29.17404
|View full text |Cite
|
Sign up to set email alerts
|

Inducing the Loss of Immunoglobulin Light Chain Production and the Rearrangement of a Previously Excluded Allele in Human Plasma B Cell Lines with Concanavalin A

Abstract: We investigated the expression of differential light chains in human B cell lines secreting immunoglobulin (Ig). When these cell lines were cultured with concanavalin A for a long period of time, a subpopulation of some but not all of these cell lines was induced to express new light chains replacing the original chain (light chain shifting). Production of the new chain, which replaces the original chain, results from a VJ rearrangement at a previously excluded allele and a dramatic reduction of the original c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
23
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 42 publications
5
23
0
Order By: Relevance
“…In fact, the expression of RAG proteins was not enhanced in the HB4C5 cells when stimulated with caffeine or okadaic acid. We have previously shown that the enhancement of RAG gene expression did not induce the light chain shifting (13). Taken together, these results suggest that the induction of light chain shifting in plasma cells by caffeine is not due to an enhancement of the RAG gene expression.…”
Section: The Amount Of Signal Broken Ends Derived From the Initiationsupporting
confidence: 65%
See 4 more Smart Citations
“…In fact, the expression of RAG proteins was not enhanced in the HB4C5 cells when stimulated with caffeine or okadaic acid. We have previously shown that the enhancement of RAG gene expression did not induce the light chain shifting (13). Taken together, these results suggest that the induction of light chain shifting in plasma cells by caffeine is not due to an enhancement of the RAG gene expression.…”
Section: The Amount Of Signal Broken Ends Derived From the Initiationsupporting
confidence: 65%
“…Although many of the VJ recombinations at the light chain loci occur in pre-B cells, recent findings suggest that light chain gene rearrangements often continue in immature-B cells and germinal center B cells (7)(8)(9)(10)(11). We also have shown that secondary VJ recombination can occur in some human plasma cell lines when stimulated with concanavalin A (ConA) 1 (12,13).…”
mentioning
confidence: 82%
See 3 more Smart Citations